2018
DOI: 10.1302/0301-620x.100b11.bjj-2018-0720
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of local antibiotic devices used to improve wound healing following the surgical management of foot infections in diabetics

Abstract: Aims Local antibiotics are used in the surgical management of foot infection in diabetic patients. This systematic review analyzes the available evidence of the use of local antibiotic delivery systems as an adjunct to surgery. Materials and Methods Databases were searched to identify eligible studies and 13 were identified for inclusion. Results Overall, the quality of the studies was poor. A single trial suggested that wound healing is quicker when a gentamicin-impregnated collagen sponge was implanted at ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…Collagen wound dressings contain collagen blended with natural and synthetic polymers such as polyethylene oxide, poly (L-lactic acid), hyaluronic acid, elastin and silk fibroin, alginate, chitosan, etc [ 73 , 81 , 82 , 83 , 84 , 85 ]. These blended fabrications have incorporated other additives such as insulin [ 86 ], antibiotics [ 87 , 88 , 89 , 90 , 91 , 92 ] or gold nanoparticles [ 93 , 94 , 95 ] and have been tested mostly in in vitro studies or small animal models of wound healing. An evidence-based review of clinical studies on antibacterial integrated collagen wound dressings indicated that most studies were limited by small sample sizes and mixed chronic wound etiologies [ 46 ].…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen wound dressings contain collagen blended with natural and synthetic polymers such as polyethylene oxide, poly (L-lactic acid), hyaluronic acid, elastin and silk fibroin, alginate, chitosan, etc [ 73 , 81 , 82 , 83 , 84 , 85 ]. These blended fabrications have incorporated other additives such as insulin [ 86 ], antibiotics [ 87 , 88 , 89 , 90 , 91 , 92 ] or gold nanoparticles [ 93 , 94 , 95 ] and have been tested mostly in in vitro studies or small animal models of wound healing. An evidence-based review of clinical studies on antibacterial integrated collagen wound dressings indicated that most studies were limited by small sample sizes and mixed chronic wound etiologies [ 46 ].…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…Collagen is also used as a surface coating to enhance moisture retention and promote cell adhesion within scaffolds/matrices [ 73 , 81 , 82 , 83 , 84 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 ]. Water retention is important to keep the wound bed moist.…”
Section: Collagen Formats and Applications In Wound Healingmentioning
confidence: 99%
“…A recent systematic review concluded there is little evidence to support routine local antibiotic delivery devices in the treatment of diabetic foot infections. 33 However, local antibiotic delivery yield very high local concentrations of antibiotics in targeted areas, especially in the presence of osteomyelitis: this approach maybe especially useful in poorly perfused tissues and 'hard-to-reach' locations. For example, the Silo technique, describes debridement delineated by MRI, drilling of bone tunnels and injection of antibiotic-loaded bio-ceramic, allowing infection control.…”
Section: Local Antibiotic Loadingmentioning
confidence: 99%
“…Gentamicin sponge, an implantable topical antibiotic agent, is approved for surgical implantation in 54 countries. Since 1985, more than 1 million patients have been treated with the sponges [1][2][3]. However, although gentamicin sponge has been studied for more than 30 years, the effectiveness of it still has been controversial [1,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%